2016
DOI: 10.4236/jmf.2016.64040
|View full text |Cite
|
Sign up to set email alerts
|

Where Do “Impatient” Mutual Funds Invest? A Special Attraction for Large Proximate Markets and Companies with Strategic Investors

Abstract: Our study examines the investment determinants of worldwide mutual funds from the perspective of economic geography. In particular, we investigate the local preferences of "impatient" mutual funds for specific countries. By analyzing a sample of 22,996 worldwide mutual funds over the period from 2005 to 2009, we demonstrate that impatient mutual funds are favorable to 1) large stock markets, 2) markets with a high level of protection for shareholders, 3) markets with familiar institutional practices, and 4) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Some studies have shown that mutual funds provide small investors with the opportunity to benefit from the capital market with minimal investments. For example, a study conducted by Dupuy et al (2016) on the Brazilian mutual fund industry found that mutual funds provided small investors with access to the capital marke.t and allowed them to diversify their portfolios with minimal investments. In terms of the use of traditional and multifactor asset pricing models to assess mutual fund performance, there have been varying findings in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that mutual funds provide small investors with the opportunity to benefit from the capital market with minimal investments. For example, a study conducted by Dupuy et al (2016) on the Brazilian mutual fund industry found that mutual funds provided small investors with access to the capital marke.t and allowed them to diversify their portfolios with minimal investments. In terms of the use of traditional and multifactor asset pricing models to assess mutual fund performance, there have been varying findings in different studies.…”
Section: Discussionmentioning
confidence: 99%